An electrically switchable wideband metamaterial absorber based on graphene at P band - Wang Liansheng (De Gruyter, 2021)
Graphene has the capability of dynamically tuning its conductivity through gate voltage. Based on this fact, an electrically switchable wideband metamaterial absorber at low frequencies is presented and investigated in this paper. Our calculated results show that its absorption is over 90% from 400 to 1,000 MHz with the Fermi level of graphene being at 0 eV and the absorption band can be switched by adjusting the Fermi level of graphene without changing its physical structure. Moreover, the surface current distribution enables us to reveal the switchable wideband absorption characteristics of our designed metamaterial absorber. At last, we prove that its absorption property is polarization-insensitive due to the rotational symmetry of the structural unit. This work may provide a further step in the development of switchable sensors and absorbers at low frequencies.